2013
DOI: 10.1007/s12288-012-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial to Compare Intravenous Iron Sucrose and Oral Iron in Treatment of Iron Deficiency Anemia in Pregnancy

Abstract: The aim of this study was to compare the efficacy and safety of intravenous iron sucrose with oral iron therapy in pregnant patients with anemia. The primary outcome of the study was increase in haemoglobin on day 7, 14 & 28 and rise of serum ferritin over 28 days. The study population consisted of 100 patients with singleton pregnancy between 24 and 34 weeks, hemoglobin levels between 7.0-9.0 gm/dL and serum ferritin levels less than 15 ng/mL. The participants in the oral group were given daily 180 mg element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 11 publications
(10 reference statements)
4
69
0
Order By: Relevance
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…13 Among other comparative studies, none demonstrated any statistically significant differences between groups across any perinatal outcomes investigated, including birth weight, gestational age, method of delivery, and postpartum haemorrhage. 11,14,16,24,30,31,37,38,54,56 Notably, the small study samples included in each of these studies limited the statistical power to detect clinically relevant differences between the two groups.…”
Section: Perinatal Outcomesmentioning
confidence: 99%
See 3 more Smart Citations